2014
DOI: 10.1080/09512748.2014.924227
|View full text |Cite
|
Sign up to set email alerts
|

Understanding ASEAN's centrality: bases and prospects in an evolving regional architecture

Abstract: There have been a number of articles about ASEAN's centrality in the regional security architecture of Asia. Yet, the notion of centrality remains undefined and under-operationalised. Implicit in the discourses of centrality is the idea of ASEAN's leadership, which in turn raises questions about ASEAN's ability to do so, given its limited capacity. This article defines ASEAN's centrality from the perspective of social network approach and argues that ASEAN's structural position in the density of networks that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…13 I regarded the proposal with some caution. There were a great number of differences between many of these parties and some had large political interests at stake.…”
Section: Indochina Policies 1983-88: Seeking An Independent Rolementioning
confidence: 99%
“…13 I regarded the proposal with some caution. There were a great number of differences between many of these parties and some had large political interests at stake.…”
Section: Indochina Policies 1983-88: Seeking An Independent Rolementioning
confidence: 99%
“…The proposal attracted some interest from the Philippines, but Indonesia indicated that such a treaty would be contrary to the spirit of Afro-Asian cooperation. 13 The SEAFET proposal, however, was an early example of interest in Southeast Asian-focused dialogue, a mode of cooperation that would emerge again in the next decade with the formation of ASEAN.…”
Section: The Cold War Era and Early Approaches Towards Regional Coopementioning
confidence: 99%
“…The Fraser Government commissioned a report on ' Australia and the Third World' and expressed some interest in efforts by developing states to seek more equitable international economic relationships, although it was not always easy for the government to reconcile this overall attitude with specific policies, for example, in trade relations with ASEAN. 13 Fraser's overall foreign policy emphasis was reflected in his government's approach towards Southeast Asia. In the period immediately after the defeat of the non-communist regimes in Indochina, the United States moved to reduce its military presence in Southeast Asia: it withdrew from its bases in Thailand although it retained a security relationship with that country and maintained its bases in the Philippines.…”
Section: Asean's 1976 Bali Summitmentioning
confidence: 99%
See 2 more Smart Citations